2015
DOI: 10.2217/epi.15.63
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavior Related to Epigenetic Differences in Preterm Infants

Abstract: Preterm birth is associated with medical problems affecting the neuroendocrine system, altering cortisol levels resulting in negative effects on newborn neurobehavior. Newborn neurobehavior is regulated by DNA methylation of NR3C1 and HSD11B2. Aim: Determine if methylation of HSD11B2 and NR3C1 is associated with neurobehavioral profiles in preterm infants. Patients & methods: Neurobehavior was measured before discharge from the hospital in 67 preterm infants. Cheek swabs were collected for DNA extraction. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 71 publications
5
30
0
Order By: Relevance
“…Thus, Profile 1 represents an optimal profile characterized by generally positive neurobehavioral responses, while Profile 6 represents a infants with atypical neurobehavioral responses. These findings are similar to profiles observed previously by others (21) and in our own research (26). To limit the number of tests being performed, the current study focused on the optimal (Profile 1) and atypical (Profile 6) profiles, while using the combination of Profiles 2-5 as the referent category in downstream analyses.…”
Section: Study Population and Nnns Profile Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, Profile 1 represents an optimal profile characterized by generally positive neurobehavioral responses, while Profile 6 represents a infants with atypical neurobehavioral responses. These findings are similar to profiles observed previously by others (21) and in our own research (26). To limit the number of tests being performed, the current study focused on the optimal (Profile 1) and atypical (Profile 6) profiles, while using the combination of Profiles 2-5 as the referent category in downstream analyses.…”
Section: Study Population and Nnns Profile Resultssupporting
confidence: 87%
“…These methylation marks can be inherited, established in-utero and/or affected by the environment throughout life, thus representing a truly integrated measure of exposure and disease susceptibility. In preterm infants, variability in (DNAm) of candidate genes have been related to medical complications such as sepsis (22), pain related stress (23,24), medical and neurobehavioral risk (25,26), and as a potential moderator of NICU environment stress on serotonergic tone and temperament (27). We have also used an epigenome-wide scan of (DNAm) in the placenta to demonstrate relationships between methylation of the FHIT and ANDKR11 genes, which had been previously linked to neurodevelopmental and behavioral outcomes, and performance on the NNNS attention scale in a cohort of term newborns (28).…”
Section: Epigenetics Refers To Mitotically and Meiotically Heritable mentioning
confidence: 99%
“…1 We 8 and others 7 have observed that methylation of the human glucocorticoid receptor promoter region, including the nerve growth factor binding site is associated with maternal mood disorders during pregnancy and infant behavior in term infants and aberrant neurobehavior in preterm infants. 20 We found altered methylation at CpG sites 7, 10, 12 and 13. This region of the human glucocorticoid receptor gene promoter is involved in the regulation of the HPA system.…”
Section: Discussionmentioning
confidence: 70%
“…It is well known that too much or too little cortisol is related to changes in behavior including behavior disorders and psychopathology (Doom & Gunnar, ). There are numerous prenatal and postnatal biological, social, and environmental factors that have been related to DNA methylation of NR3C1 altering its expression resulting in overproduction or underproduction of cortisol levels (Glover, O'Connor, & O'Donnell, ; Lester, Conradt, & Marsit, ; Romens et al., ; Tyrka et al., ).…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%
“…For example, the hypothalamic-pituitary-adrenal (HPA) axis is a consistent topic of studies of development and programming as it plays a central role in stress reactivity and can be programmed by various environmental factors. (Glover et al, 2010;Lester et al, 2015;Meaney, 2010). Although the GR (encoded by NR3C1) is a key gene in this pathway, a number of other genes also are involved.…”
Section: Approaches To the Study Of Dna Methylationmentioning
confidence: 99%